Design and operation of single- and multi-deep shuttle-based storage and retrieval systems (SBS/RS) - Lerher, Tone; Marolt, Jakob; Sgarbossa, Fabio; Ekren, Banu Y.; Dukic, Goran (Springer, 2024)
With the rapid growth of e-commerce practices, the efficient management of warehouses and fulfilment centres has become crucial in supply chain operations. One effective strategy for achieving this efficiency is the digital transformation of warehouses through automation. In particular, shuttle-based storage and retrieval systems (SBS/RS) have gained significant attention due to their ultra-high transaction process capability. However, ongoing research focuses on enhancing the operating performance and cost efficiency of these SBS/RS designs. This chapter presents mathematical modelling approaches for estimating the performance of single- and multi-deep SBS/RS designs. These models provide valuable insights for designing warehouses that optimize transaction process rates while ensuring a balanced utilization of elevators and shuttles in the system, tailored to meet the specific requirements of the warehouse. By leveraging these modelling techniques, warehouse managers can make informed decisions regarding the design and configuration of SBS/RSs to improve overall operational efficiency and productivity.
Keywords: 46 Information and Computing Sciences; 4609 Information Systems; 7 Affordable and Clean Energy